2001
DOI: 10.1002/1521-4141(200103)31:3<734::aid-immu734>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of type 2 cytokines in chronic proliferative dermatitis (cpdm) mutant mice and resolution of inflammation following treatment with IL-12

Abstract: Chronic proliferative dermatitis (cpdm) is a spontaneous mutation that results in eosinophilic inflammation in multiple tissues, including the skin. To determine the mechanisms underlying the eosinophilic inflammation, the expression of cytokines in the skin was determined. There was increased expression of IL‐4, IL‐5, IL‐13, and granulocyte‐macrophage colony‐stimulating factor in the skin of cpdm/cpdm mice, and no change in IL‐10 and TNF expression. Supernatants of cultured spleen cells of cpdm/cpdm mice cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 47 publications
3
37
1
1
Order By: Relevance
“…5E). The increase of cytokines produced by Th2 cells including IL-5 and IL-13 in the skin and spleen of cpdm mice plays a role in the pathogenesis of dermatitis (36). We confirmed that the amount of IL-5 and IL-13 mRNA was higher and that of Th1 cytokines IL-12 and IFN-g was lower in the spleen of cpdm mice than in WT mice.…”
Section: Reduction Of Macrophage Neutrophil and Mast Cell Infiltratmentioning
confidence: 58%
See 1 more Smart Citation
“…5E). The increase of cytokines produced by Th2 cells including IL-5 and IL-13 in the skin and spleen of cpdm mice plays a role in the pathogenesis of dermatitis (36). We confirmed that the amount of IL-5 and IL-13 mRNA was higher and that of Th1 cytokines IL-12 and IFN-g was lower in the spleen of cpdm mice than in WT mice.…”
Section: Reduction Of Macrophage Neutrophil and Mast Cell Infiltratmentioning
confidence: 58%
“…Moreover, suppressed IFN-g secretion, which has been reported in cpdm mice (36), might be involved in the pathogenesis of dermatitis. Because IFN-g is produced by Th1 cells and is able to induce Th1 cells, it is possible that in our study, IFN-g ameliorated the dermatitis by inducing Th1 cells in cpdm mice.…”
Section: Ifn-a Increased the Amount Of Lubac And Ameliorated Dermatitmentioning
confidence: 99%
“…The mutant phenotype includes multiorgan inflammation with eosinophilia, defective T H 1 cytokine production, splenomegaly and dermatitis with granulocytic infiltrates, ortho-and parakeratotic hyperplasia, and follicular dystrophy. 1,2 Peyer's patches are absent in adult mice, and remaining secondary lymphoid organs lack B-cell follicles, follicular dendritic cells and germinal centers. The B-and T-cell areas of the spleen are poorly defined, and the marginal zone is absent.…”
Section: Introductionmentioning
confidence: 99%
“…Along with dermatitis, cpdm mice develop systemic inflammation and adaptive immune defects, such as splenomegaly, disrupted secondary lymphoid organ development, and inflammatory infiltrates throughout the body. Skin disease in cpdm mice was initially considered a model of human AD, given the similar histopathological findings, the prominent Th2 cytokine profile in the skin and spleen, and the associated eosinophilia (35). However, the observations that neither depletion of eosinophils via neutralizing anti-IL-5 Ab administration (36) nor genetic ablation of IL-4R and IL-13R (37) alleviated skin inflammation suggested that type 2 immune responses could be manifestations of alternate mechanisms driving skin disease.…”
mentioning
confidence: 99%